2019
DOI: 10.1186/s12879-019-4409-1
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of ceftazidime-avibactam in the treatment of infections due to Carbapenem-resistant Enterobacteriaceae

Abstract: Background Carbapenem-resistant Enterobacteriaceae (CRE) represent an important global threat. The aim of this study is to describe the clinical course and outcomes of patients with CRE infections treated with ceftazidime-avibactam (CAZ-AVI) compared to patients treated with other agents. Methods A retrospective cohort study of patients with established CRE infections from January 2017 until August 2018 was conducted. All patients who received… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 25 publications
1
46
1
2
Order By: Relevance
“…The focus of infection in the 83% (419/503) of patients was bacteremia; only in 3 of these 6 retrospective studies bacteremia was aggregated with other focus of infection: In the study by King et al [26], two fifths of the patients (23/60) had bacteremia, in the study by Sousa et al [8], almost half of the patients (26/57) have bacteremia. In the study by Alraddadi et al [27], more than a half of patients (22/38) have bacteremia.…”
Section: Study Selection and Characteristicsmentioning
confidence: 94%
See 1 more Smart Citation
“…The focus of infection in the 83% (419/503) of patients was bacteremia; only in 3 of these 6 retrospective studies bacteremia was aggregated with other focus of infection: In the study by King et al [26], two fifths of the patients (23/60) had bacteremia, in the study by Sousa et al [8], almost half of the patients (26/57) have bacteremia. In the study by Alraddadi et al [27], more than a half of patients (22/38) have bacteremia.…”
Section: Study Selection and Characteristicsmentioning
confidence: 94%
“…Non-clinical improvement was evaluated in only 4 studies [6,8,26,27], including 186 patients and microbiological failure was evaluated in only 4 studies [5,8,26,27], including 363 patients (Table 2). Therefore, due to the small number of patients, we did not proceed to quantitative synthesis for the secondary outcomes.…”
Section: Mortalitymentioning
confidence: 99%
“…On the other hand, CAZ/AVI was associated with better survival rates in patients with bacteraemia who required rescue treatment in infections caused by KPC-producing Enterobacteriaceae [89]. In case of infection caused by a CAZ/AVI-susceptible OXA-48 strain, CAZ/AVI could be an option to treat it [90].…”
Section: Current and Future Solutionsmentioning
confidence: 99%
“…Bacteria belonging to Enterobacterales, such as Escherichia coli, Klebsiella pneumoniae, Enterobacter, Citrobacter, Serratia, Proteus, and Morganella, often cause nosocomial infections. 1,2 During the last decade, the emergence of carbapenem-resistant Enterobacteriaceae (CRE), which led to limited treatment options, has become the main cause of clinical anti-infective treatment failure. 3,4 It is worth noting that carbapenem-resistant Enterobacter cloacae (CR-ECL), which is one of the most common species that has been focused on in studies of a single species of Enterobacterales, 5 has been reported in many countries such as Korea, the United States, India, and China.…”
Section: Introductionmentioning
confidence: 99%